Partial Stereotactic Ablative Radiotherapy Boost Before Conventional Radiotherapy (P‐SABR) for Large (> 5 cm) Unresectable Stage III Nonsmall Cell Lung Cancer - Yun Bai; Xianshu Gao; Shangbin Qin; Shanshi Li; Mingwei Ma; Xi Cao; Feng Lyu; Jiayan Chen; Xin Qi; Siwei Liu; Yan Gao; Hongzhen Li; et al. (Thoracic Cancer)
ABSTRACT Objective Stereotactic ablative radiotherapy (SABR) is renowned for its high local control (LC) rates. Nonetheless, for tumors that are either large in volume or in close proximity to critical organs at risk, the application of SABR to the entire tumor becomes impractical. This study aims to evaluate the efficacy and safety of partial SABR boost before conventional radiotherapy (P‐SABR) for the treatment of large (> 5 cm) unresectable stage III nonsmall cell lung cancer (NSCLC). Methods From April 2014 to January 2024, 44 patients with > 5 cm unresectable T3‐4N0‐3M0 stage III NSCLC were analyzed. The median diameter was 9 cm (5.2–22.7 cm). The P‐SABR plan is combined with a partial SABR boost part and a conventional fractionated radiotherapy (CFRT) part. In the partial SABR boost plan, the prescription dose for planning target volume (PTV) was 1.8–3 Gy per fraction over 3–4 fractions, and the artificially delineated gross tumor boost volume (GTVb) within GTV received a simultaneously integrated SABR dose (6 or 8 Gy per fraction). In the following CFRT plan, the median dose for the entire PTV was 54 Gy in 22 fractions. For the synthetic P‐SABR plan, the median cumulative dose delivered to the PTV was 62.1 Gy, while the median cumulative dose to the GTVb was escalated to 78 Gy. Results The median follow‐up time was 36 months (95% CI, 14.6–57.4 months). The LC rates at 1 and 2 years were 90.2% and 76.8%, respectively. The median OS was 47.0 months (95% CI, 16.8–77.2 months) and 15.0 months (95% CI, 6.0–24.0 months) for the chemoradiotherapy and radiotherapy groups, respectively. Univariate analysis showed that P‐SABR combined with immunotherapy was associated with significantly longer OS (HR, 0.163; 95% CI, 0.038–0.704). Only one (2.3%) patient experienced grade 3 acute pneumonitis. Conclusions The P‐SABR treatment has shown a high rate of LC and tolerable toxicity in patients with large unresectable stage III NSCLC.